Reading Aloud: Upaya Membangun English Literacy Anak-Anak Desa Trembes, Kecamatan Malo, Kabupaten Bojonegoro - Ima Kulama Gutami; Anggita Refida Prismutitomi; Jovanny Cynthia Laverda; Khoirun Nikmah; Muhammad Jundullah; Nur Rochmadhoni; Ratna Nidya Primasari; Afifah Dewi Kurniati; Aista Bella; Mayla Zainun Nafi'ah; Agus Syaifudin; Izza Himmatul Ulya; Elisa Indriyaningsih; Siti Nur Rohmah; Sri Ningsih; Chyntia Heru Woro Prastiwi (IKIP PGRI Bojonegoro, 2021)
This article is the result of Holistic Program for Village Empowerment and Development in Trembes Village, Malo District, Bojonegoro Regency. In the space structural plan of Bojonegoro Regency, Malo District will be the Reagional Service Centre, while Trembes Village is set to be the Local Service Centre. The strategic potential of this area must be accompanied by the improvement of human resources since in the early ages. During covid 19 pandemic, more or less 80 kids in the elementary school age tended to play and their parents got difficulties in guiding their studies, particularly in English subject that becomes one of literacy indicators. Moreover, no English private course is available there. By taking the theme of “Reading Aloud: An Effort for Developing English Literacy of Children in Trembes Village, Malo District, Bojonegoro Regency”, this community service program aimed at developing English Literacy among the kids in Trembes Village through a simple activity but meaningful namely Reading Aloud. This routine program was carried out every Sunday at 09.00-11.00 in August-November 2021 by prioritizing on the activity of reading aloud for shaping English Literacy. The activities of reading aloud bilingual books, giving English materials, as well as varying indoor and outdoor learning had developed the English literacy of children in terms of vocabulary, grammar, and practical uses.Artikel ini merupakan hasil dari pelaksanaan Program Holistik Pembinaan dan Pemberdayaan Desa (PHP2D) di Desa Trembes, Kecamatan Malo, Kabupaten Bojonegoro. Dalam rencana struktur ruang wilayah Kabupaten Bojonegoro, wilayah Kecamatan Malo akan menjadi Pusat Pelayanan Kawasan (PPK), sedangkan Desa Trembes menjadi Pusat Pelayanan Lokal (PPL). Potensi strategis wilayah ini harus diiringi dengan peningkatan kualitas SDM (Sumber Daya Manusia) sejak dini. Selama pandemic covid 19, kurang lebih 80 anak usia SD di Desa Trembes cenderung bermain dan para orang tua mengalami kesulitan dalam mendampingi belajar, terutama mata pelajaran Bahasa Inggris yang merupakan salah satu indikator literasi. Selain itu, tidak adanya lembaga kursus Bahasa Inggris di Desa Trembes juga berkontribusi terhadap rendahnya literasi berbahasa Inggris. Dengan mengambil tema “Reading Aloud: Upaya Membangun English Literacy Anak-Anak Desa Trembes, Kecamatan Malo, Kabupaten Bojonegoro”, kegiatan ini pengabdian kepada masyarakat ini bertujuan membangun literasi Bahasa Inggris anak-anak SD di Desa Trembes melalui kegiatan sederhana namun sangat berarti yaitu dengan Reading Aloud. Kegiatan yang dilaksanakan setiap hari minggu jam 09.00-11.00 sejak Agustus hingga November 2021 ini mengutamakan aktivitas reading aloud untuk membentuk English Literacy. Rutinitas kegiatan yang diawali dengan membaca nyaring buku cerita dwibahasa, lalu memberikan materi Bahasa Inggris, serta variasi suasana indoor maupun outdoor telah mampu membentuk dan mengembangkan English Literacy anak-anak Desa Trembes dalam hal kosakata, tata Bahasa, maupun penggunaan praktis.